2021
DOI: 10.3389/fnins.2021.624472
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 0.01% Atropine on Adult Myopes’ Contrast Sensitivity

Abstract: PurposeAtropine at a low concentration is considered a safe and effective treatment to mitigate myopia progression. However, the potential unwanted side effects of administering atropine at a low dose on visual functions other than best corrected visual acuity has not been investigated. In this study, we investigate the short-term (12,16, and 20 h) and long-term (1, 2, and 4 weeks) effects of 0.01% atropine (i.e., 0.1 mg/ml) on contrast sensitivity (CS) in patients with myopia.MethodsThirty adults (23.33 ± 2.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
(60 reference statements)
1
2
0
2
Order By: Relevance
“…Our study even showed a tendency towards improved CS under mesopic conditions after administration of atropine, presumably due to the enlarged pupil 28 . Our results regarding contrast sensitivity under the influence of atropine are consistent with findings from earlier research: in a study that investigated the short-term and long-term effects of 0.01% atropine on CS, no significant reduction in CS was observed 18 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study even showed a tendency towards improved CS under mesopic conditions after administration of atropine, presumably due to the enlarged pupil 28 . Our results regarding contrast sensitivity under the influence of atropine are consistent with findings from earlier research: in a study that investigated the short-term and long-term effects of 0.01% atropine on CS, no significant reduction in CS was observed 18 .…”
Section: Discussionsupporting
confidence: 92%
“…Die vorliegenden Ergebnisse bez. der Kontrastempfindlichkeit unter Atropineinfluss decken sich mit früheren Erkenntnissen: In einer Studie, die die Kurzzeit-und Langzeiteffekte von 0,01 % Atropin auf KE untersucht hat, konnte keine signifikante Reduktion der KE festgestellt werden [18].…”
Section: Kontrastempfindlichkeit (Visual Function Analyzer)unclassified
See 2 more Smart Citations
“…This computerized device has been previously applied in studies concerning CSF after the use of atropine (Cheng et al, 2021). Contrast sensitivity was measured with sinusoidal gratings of spatial frequencies (1.5, 3, 6, 12, 18, and 24 cycles/degree) which were 3.0 × 3.0 at a viewing distance of 2 m. To minimize the edge effect, a 0.5° Gaussian ramp was added to blend the stimulus into the background.…”
Section: Visual Functionmentioning
confidence: 99%